Science mapping for concrete composites as radiation shielding: A review - Ardiansyah, Ardiansyah; Tahir, Dahlang; Heryanto, Heryanto; Armynah, Bidayatul; Salah, Hassan; Sulieman, Abdelmoneim; Bradley, D.A. * (Elsevier, 2023)
This paper provides a comprehensive bibliometric analysis to better understand the evolution of concrete composite as a radiation shielding research from when it was first published in 1949 to October 26, 2022. This study was conducted based on the Scopus database, and the publications analyzed a total of 541 documents. The data in this paper is visualized using the VOSviewer and Tableau to perform bibliometric analysis and scientific mapping. The analysis results show that published documents have continued to increase in recent years and are dominated by articles. Some countries show productivity and influence in their country/region with the broadest range of partners. This study presents the most contributed journals and the most frequently cited documents. In addition, keyword analysis was carried out to find the hotspots on this research topic. This paper helps scholars to understand the evolution of concrete composite as a radiation shielding research from a bibliometric perspective and inspires them to develop new concrete composite with high stability absorption properties from waste or natural material to replace concrete Lead (Pb)-based.